UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) SISWA KELAS X E6 SMA NEGERI 6 DENPASAR TAHUN PELAJARAN 2023/2024 - I Komang Sukendra; Nikmatul Atiyah; I Wayan Suwiasa (Widyadari, 2024)
NHT cooperative learning focused on cooperation in groups, student centered learning and with the numbering model will make the students more active in classroom discussions. This classroom action research aims to find out whether the application of the Numbered Head Together (NHT) cooperative learning model can improve mathematics learning outcomes and to describe the implementation of learning using the NHT. The subjects in this research were class X E6 students at SMA Negeri 6 Denpasar for the 2023/2024 academic year. This classroom action research was carried out in two cycles which included initial reflection, action planning, action implementation, observation/data collection, and reflection. Data collection was carried out through observation and written assessments. The instruments used were observation sheets and description questions. The data analysis technique used is descriptive analysis. Based on the results of observations, the average percentage of student achievement of learning objectives increased from cycle I of 69.05% to 78.57% in cycle II. Based on these results, it is concluded that the application of the NHT type cooperative learning model can improve mathematics learning outcomes in Trigonometry material for class X E6 students at SMA Negeri 6 Denpasar for the 2023/2024 academic year.